(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
The current architecture of computers calls for applications to be prepared to use more than one processing core. This paper will verify if the current programming model, i.e. object oriented, allows programs to make good use of this architecture, showing possible reasons to seek alternatives to accompany the architectural evolution. It will bring a brief explanation of the history of programming languages, contextualizing the reasons that led the market to the objectoriented paradigm. Through these reasons and the evolution of architecture, a projection will be made on some reasons that may cause the actual style of programming to be replaced. It will examine the concepts of concurrency and parallelism that are becoming more necessary with this new architecture. This examination will be made in the current model, in Java, and bringing as a possible alternative, the point of view of the functional model of pure and lazy evaluation, specifically in the Haskell language.